Cardiac arrest survivors lost to follow-up after 3-Months, 6-Months and 1-Year. (May 2020) - Jaramillo, Stephany; Flickinger, Katharyn L.; Repine, Melissa; Pacella-LaBarbara, Maria; Callaway, Clifton W.; Koller, Allison; Cullison, Kevin; Rittenberger, Jon C.
Abstract: Background: Long-term assessment of global functional outcomes in cardiac arrest (CA) survivors allows for evaluation of acute care practices and referral to rehabilitation services. Given that many post-CA patients are lost to follow-up (LTFU), we explored whether these patients are systematically different from those who complete follow-up based on demographic, resuscitation and outcome characteristics. Methods: We conducted a prospective cohort study of 168 English-speaking CA survivors between 9/25/2016 and 5/31/2018. We measured demographic data and global functional outcomes using Modified Rankin Scale (mRS), and Cerebral Performance Category (CPC) in-person at hospital discharge, and via telephone at 3-, 6-months, and 1-year. We compared patients LTFU (e.g., failure to contact or refused to follow-up) with those contacted. Patients who were hospitalized, in a rehabilitation facility, missed by the research team, or dead were considered not eligible for follow-up. Results: Of the 116 patients eligible for follow-up at 3-months, the majority completed follow-up (n = 69; 59.5%) and 47 (40.5%) were LTFU. Conversely, at 6-months and 1-year, fewer subjects were assessed (42% and 47%) compared to those who were LTFU (58% and 53%), respectively. At 3-months, LTFU patients were younger, unmarried, and had longer ICU stay. At 6-months and 1-year, LTFU patients were primarily male, had a non-shockable primary rhythm, and non-cardiac arrest etiologies. Conclusions: Over one-third of patients are LTFU during the first year after CA, and differences emerged for demographics and characteristics of the event. Future research should account for the informative, non-random distribution of patients LTFU.